2016
DOI: 10.1161/strokeaha.116.014078
|View full text |Cite
|
Sign up to set email alerts
|

Preventive Suboccipital Decompressive Craniectomy for Cerebellar Infarction

Abstract: Background and Purpose-No evidence is available on the benefits of preventive suboccipital decompressive craniectomy (SDC) for patients with cerebellar infarction. The purpose of this matched case-control study was to investigate whether preventive SDC was associated with good clinical outcomes in patients with cerebellar infarction and to evaluate its predisposing factors. Methods-Between March 2007 and September 2015, 28 patients underwent preventive SDC. We performed propensity score matching to establish a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 29 publications
(30 reference statements)
3
32
0
Order By: Relevance
“…Kim and co-workers published results of a retrospective matched case-control study [63]. The surgical patients were treated with suboccipital DC and additionally 50% received an external ventricular drain (EVD) and 57% a debridement of infarcted tissue.…”
Section: Infratentorial Malignant Ischemic Stroke In Adultsmentioning
confidence: 99%
“…Kim and co-workers published results of a retrospective matched case-control study [63]. The surgical patients were treated with suboccipital DC and additionally 50% received an external ventricular drain (EVD) and 57% a debridement of infarcted tissue.…”
Section: Infratentorial Malignant Ischemic Stroke In Adultsmentioning
confidence: 99%
“…In comparison to the role of DHC for malignant MCA infarction, the role of suboccipital decompressive craniectomy (SDC) for malignant cerebellar infarction is less documented in literature. As described in Beez et al (31), the best available evidence derives from one retrospective case-control study, several case series, and a recent meta-analysis (32)(33)(34)(35).…”
Section: Suboccipital Craniectomymentioning
confidence: 99%
“…The retrospective matched case control study, published by Kim and colleagues, compared clinical outcomes between 28 patients who underwent preventive SDC for cerebellar infarction with 56 patients who did not undergo the procedure with cerebellar infarction (32). Selection criteria included initial GCS ≥9 without clinical deterioration within 72 hours from onset and a cerebellar infarction volume ratio between 0.25 and 0.33 on neuroimaging (volume ratio = cerebellar infarction volume / total cerebellar volume).…”
Section: Suboccipital Craniectomymentioning
confidence: 99%
“…SDC has been reported in the literature since as early as 1956 [8,9], with subsequent work by Lehrich, et al [10] in 1970 further demonstrating the potential role in mortality reduction. Current evidence is still limited to retrospective case series [11,12], with no randomised control trials available. A recent meta-analysis, published in 2017, identified eleven observational studies with 283 patients and found that SDC has benefit as a lifesaving procedure, but patient selection based on certain factors such as age and unilateral infarction could further improve outcomes, however further evidence is still required [13].…”
Section: Casementioning
confidence: 99%